Analisa Bibliometrik Terhadap Kinerja Keuangan - Muhammad Nizar Firmansyah; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
There have been several scientific publications related to financial performance; Financial performance is a description of a company's financial condition in a certain period regarding aspects of raising funds and distributing funds, which are usually measured by indicators of capital adequacy, liquidity and profitability. This article aims to provide information regarding research trends that have been published on the topic of financial performance in the period 2018-2023. The method used in this research is to identify the number of journals using Harzing's Publish or Perish software, as well as bibliometric analysis using VOSviewer. The research results showed that there were 54 publications with 16 citations and 2.67 cites/year that discussed financial performance. There are five main clusters based on the results of bibliometric analysis. This article also provides information related to research topics that have not been widely conducted so that it can provide benefits to stakeholders who may need it for further research.